Peran Perceived Organizational Support pada Psychological Capital Guru - Nurhasni Nurhasni; Tuti Rahmi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
The purpose of this study was to examine the contribution of perceived organizational support to teachers’ psychological capital. This study employed a quantitative approach with a correlational design to analyze the relationship and the magnitude of contribution between the variables under investigation. The participants of this study were teachers working in one district in West Sumatra Province, which was selected to represent the organizational conditions of educational institutions in the region. The sampling technique used was area sampling, refined with proportional sampling, resulting in a total sample of 302 teachers from various educational units. Data were collected using the Psychological Capital Questionnaire to measure teachers’ psychological capital and the Survey of Perceived Organizational Support to assess teachers’ perceptions of organizational support. The collected data were analyzed using statistical analysis techniques to determine the contribution of the independent variable to the dependent variable. The results of the data analysis indicated that perceived organizational support contributed 23.1% (R² = 0.231) to teachers’ psychological capital. These findings suggest that organizational support plays a significant role in enhancing teachers’ positive psychological conditions in carrying out their professional duties.